Four prognoses about the dream matter in Fernando Lindote (Palíndromo, 2022)
Fernando Lindote's painting refers to a dreamlike dimension, less because the artist equates his plastic images with figurations of dreams and more because he realizes through his own pictorial visuality a kind of oneiric experience. The notion of prognosis refers to the sense of carrying forward a certain type of knowledge, becoming a way of questioning how this feat happens from the formal and imagery point of view, in addition to problematizing the temporal implications, the references and visual articulations, as well as the decantations poetic and conceptual. The reflection unfolds in four parts. The first highlights the slippery and slippery character as a pictorial feat of this artist, then discusses the flickering effects that make use of certain works by Lygia Clark and Lygia Pape. Then he considers the flow of different temporalities that affect each work and, finally, recognizes his painting as an imaginative machine that both triggers and is triggered by its mnemonic singularity and its metamorphic processes.
Keywords: Prognosis; Fernando Lindote; Oneiric Figuration; Contemporary Painting